Hydroxyurea for Malignant Pertussis in Critically Ill Children - Matthieu Blanc, MD; Clémence Marais, MD, MSc; Alexandre Debs, MD; Vladimir L. Cousin, MD; Pierre Tissières, MD, DSc; on behalf of the Paris Saclay Neonatal and Pediatric ICU Research Alliance (PANDORA) Study Group; Melissa Beggaz, MD; Matthieu Blanc, MD; Claire Boithias, MD, MSc; Charlotte Brognion, MD; Diane Carriere, MD, MSc; Ramy Charbel, MD; et al. (Critical Care Explorations)
OBJECTIVES:. Malignant pertussis, the most severe manifestation of Bordetella pertussis infection, is characterized by multiple organ failure and a high mortality rate despite advanced intensive care measures. Hyperleukocytosis is the hallmark of malignant pertussis and necessitates urgent and aggressive interventions. Among the therapeutic options, leukoreduction via whole blood exchange (BE) transfusion has been associated with significant procedural risks and potential clinical deterioration. Hydroxyurea was recently proposed as a pharmacological alternative for leukoreduction. This study reports our clinical experience with hydroxyurea as an alternative to BE in managing infants with malignant pertussis admitted to a PICU. DESIGN:. Prospective case series. SETTING:. A referral PICU in France. PATIENTS:. Critically ill infants (n = 27) with severe pertussis infection. INTERVENTIONS:. Hydroxyurea therapy or BE transfusion. MEASUREMENTS AND MAIN RESULTS:. We reviewed all critically ill infants admitted to our unit for severe pertussis between January 2017 and July 2024. The primary outcome was 28-day survival, and the secondary outcome was the efficacy of hydroxyurea on blood leukocyte count reduction. Among the 27 infants admitted for severe pertussis, 12 exhibited features of malignant pertussis. Of these, seven were treated with hydroxyurea and five with BE. The majority of infants were term and under 3 months old. All patients required ventilatory support, with eight on invasive mechanical ventilation and three receiving extracorporeal membrane oxygenation therapy. Overall mortality was three of 12 (25%). Hydroxyurea was administered at a dose of 20 mg/kg/d for a median duration of 12 days. Hyperleukocytosis was successfully reduced within 7 days. CONCLUSIONS:. Hydroxyurea is an alternative therapy for malignant pertussis infection that can efficiently address hyperleukocytosis with limited mortality.